Quantitative analyses of sacroiliac biopsies in spondyloarthropathies: T cells and macrophages predominate in early and active sacroiliitis— cellularity correlates with the degree of enhancement detected by magnetic resonance imaging. Issue 2 (1st February 2000) - Bollow, M; Fischer, T; Reiβhauer, H; Backhaus, M; Sieper, J; Hamm, B; Braun, J
Abstract : OBJECTIVE: Sacroiliitis is a hallmark of the spondyloarthropathies (SpA). The degree of inflammation can be quantified by magnetic resonance imaging (MRI). The aim of this study was to further elucidate the pathogenesis of SpA by quantitative cellular analysis of immunostained sacroiliac biopsy specimens and to compare these findings with the degree of enhancement in the sacroiliac joints (SJ) as detected by dynamic MRI. METHODS: The degree of acute sacroiliitis detected by MRI after intravenous administration of gadolinium-DTPA was quantitatively assessed by calculating the enhancement observed in the SJ and chronic changes were graded as described in 32 patients with ankylosing spondylitis (n=18), undifferentiated SpA (n=12) and psoriatic arthritis (n=2). Back pain was graded on a visual analogue scale (VAS, 0–10) and disease duration (DD) was assessed. Shortly after MRI, SJ of patients with VAS > 5 were biopsied guided by computed tomography. Immunohistological examination was performed using the APAAP technique; only whole sections > 3 mm were counted. RESULTS: By MRI, chronic changes ⩽ grade II were detected in nine patients (group I, DD 2.5 (SD 2.9) years) and > II in 13 patients (group II, DD 7.3 (SD 4.8) years), while enhancement < 70% was found in eight (group A, DD 5.6 (SD 3.3) years) and > 70% in 12 patients (group B, DD 4.7 (SD 5.8) years). The relative percentage of cartilage (78–93%), bone (7–18%) and proliferating connective tissue (1–4%) was comparable between the groups (range). There were more inflammatory cells in group I compared with group II (mean (SD) 26.7(20.1) versus 5.3 (5.2), p=0.04) and group A compared with B (21.8 (17.3) versus 6.0 (5.6), p=0.05) cells/10 mm 2 ), T cells (10.9 (8.5)) being slightly more frequent than macrophages (9.6 (16.8/10 mm 2 )). Clusters of proliferating fibroblasts were seen in three and new vessel formation in seven cases. CONCLUSION: This study shows that T cells and macrophages are the most frequent cells in early and active sacroiliitis in SpA. The correlation of cellularity and MRI enhancement provides further evidence for the role of dynamic MRI to detect early sacroiliitis.